Photocatalytic activity of Eu-doped ZnO prepared by supercritical antisolvent precipitation route: When defects become virtues. (10th June 2022) - Sacco, Olga; Franco, Paola; De Marco, Iolanda; Vaiano, Vincenzo; Callone, Emanuela; Ceccato, Riccardo; Parrino, Francesco
Highlights: Eu-doped ZnO at different Eu content were synthetized by SAS process. Eu-doped ZnO provides novel defect sites and higher hydrophilicity. Photocatalytic activity was assessed under UV light. The optimal Eu content for crystal violet and ferulic acid degradation was 1 mol%. A lower hydrophilicity induced a higher vanillin selectivity. Abstract: The aim of this work is to determine the structural and optical properties of Eu-doped ZnO powders prepared by supercritical antisolvent precipitation route (SAS) and to correlate the physico-chemical features with the photocatalytic activity under UV light. Raman and EPR spectroscopy highlight the introduction of novel defects (mainly singly and doubly ionized oxygen vacancies, and oxygen interstitials) on the Eu-doped ZnO samples, which confer higher hydrophilicity to the doped samples with respect to bare ZnO, as evidenced by FT-IR analysis. Additionally, photoluminescence spectra show that the presence of Eu 3+ totally quenches the visible light emission typical of bare ZnO, which mainly results from the recombination of photogenerated holes at defective sites. The prepared samples were tested both for the photocatalytic degradation of crystal violet dye (CV) and for the partial oxidation of ferulic acid under UV irradiation. The photocatalytic activity results evidence of a higher ability of Eu-doped photocatalysts to degrade CV and ferulic acid, while higher selectivity values towards vanillin are obtained in the presence of bare ZnO. The higher activity of Eu-doped ZnO photocatalysts is linked to the stabilization of photogenerated holes and to their higher hydrophilicity, both brought by the generation of defective sites induced by the presence of Eu 3+ ions within the ZnO lattice.